Finite Element Analysis of a Lightweight Milling Cutter for Metal Additive Manufacturing - Hanzl, Pavel; Zetek, Miroslav; Rulc, Vojtech; Purs, Hynek; Zetkova, Ivana (Manufacturing Technology Journal, 2019)
Previous work has proposed a process for implementing a lattice structure into a milling cutter body based on clustering in the milling cutter with modified main dimensions of a BCC cubic lattice structure cell. A finite element analysis model has been created to predict the strain and deformation in the struts of the lattice. The prediction made according to static loads demonstrates that the concept of a lightweight cutter meets the strength requirements, though its stiffness does not reach the fully-filled version. The methodologies for creating the FE model are described in this paper. HyperWorks with OptiStruct were used for these analyses. Local stiffness could be improved by varying the strut diameter or using a different type of basic cell for the lattice structure in problematic locations, especially in the area of the connection between the shell of the cutter and the lattice structures.
Keywords: Milling Tool; Topological Optimization; Direct Melting Laser Sintering; Metal Additive Manufacturing